Nonsyndromic aplasia cutis congenita: a case report - Hassan, Md Kamrul; Paul, Amal Chandra; Fatema, Kaneez; Islam, Md Raisul (Faridpur Medical College Journal, 2015)
Nonsyndromic aplasia cutis congenita is a condition in which babies are born with localized areas of missing skin. These areas resemble ulcers or open wounds, although they are sometimes already healed at birth. Lesions most commonly occur on the top of the head (skull vertex). In some cases, the bone and other tissues under the skin defect are also underdeveloped. If the baby is born by cesarean section, then the patient's attendants recognize the wound as an injury which might be performed by the surgeon at the time of cesarean section. We are reporting this type of a case whose father attempted to take legal procedure against the surgeon, but finally he understood that this was a congenital disease of his baby. Faridpur Med. Coll. J. 2014;9(1): 56-57